Effects of Chromium Ore Tailings on Growth and Physiological Activities of Mesua ferrea L. Issue 5 (3rd July 2016) - Panda, Swati Sucharita; Basu, Aradhana; Dhal, Nabin Kumar
ABSTRACT: A greenhouse pot experiment was conducted to evaluate the feasibility of using a native ornamental plant, Mesua ferrea L. as phytostabilizer for chromium ore tailings (COT) and to assess the metal accumulation capacity. Different ratios of soil and COT were taken in pots and sowed with seeds of M. ferrea . Plants were harvested at various intervals and separated into roots and shoots for analysis of metal concentrations and physiological characteristics of the plants. The study revealed that the plant has great tolerance and stronger ability to accumulate Cr. The results suggested an increase in growth, chlorophyll content, antioxidant activities, as well as metal accumulation capacity of M. ferrea with increasing proportion of COT in the soil. This indicates the plant's efficiency to overcome any stress generated due to excess of chromium as well as other heavy metals. The order of accumulation of heavy metals was observed to be Fe>Cr>Ni>Cd>Co. The accumulation of Cr was higher in root compared to that in shoot. M. ferrea has found to be potential as a native species candidate for phytostabilization of chromium mine tailings.